2012
DOI: 10.1074/jbc.m112.339127
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is a Protective Mechanism for Human Melanoma Cells under Acidic Stress

Abstract: Background: Human melanoma cells are able to sustain low pH conditions characterizing many solid tumors. Results: Acidic stress in melanoma cells induces reduced nutrients uptake, inhibition of mammalian target of rapamycin, and activation of autophagy. Conclusion: Melanoma cells activate autophagy as a protective and adaptive response to acidic stress. Significance: Adaptation to acidosis via autophagy confirms the feasibility of anticancer therapy targeting autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
133
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 77 publications
16
133
1
1
Order By: Relevance
“…Intracellular pH changes are typical for many processes, such as starvation (12) and ischemia (13), and importantly many of them are known to be activators of mitophagy (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular pH changes are typical for many processes, such as starvation (12) and ischemia (13), and importantly many of them are known to be activators of mitophagy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, other physiological processes that induce mitophagy, such as hypoxia and starvation, also induce mild acidification of the cytosol (12-16). Changes in intracellular pH activates autophagy (17,18).To investigate the effect of the cytosolic changes on mitophagy we investigated the effect of FCCP and nigericin on pH cyt and how these changes promote the mitochondrial translocation to lysosomes. We found that acidification of cytosol caused by nigericin can trigger autophagy and mitophagy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28,45,59 Briefly, following IL13 treatment of hTEC cultured at the air-liquid interface, cells were incubated with 50 mM of chloroquine or 100 mM of bafilomycin A 1 for 3 h in the absence or presence of IL13. Subsequently, immunoblot analysis was used to quantify the change in LC3-II to actin ratio, and in parallel samples cells were fixed for LC3 puncta immunostaining.…”
Section: Autophagy Flux Assaymentioning
confidence: 99%
“…Indeed, a body of evidence suggests that autophagy is induced in cancer cells by microenvironmental stresses including growth factor withdrawal (through MTORC1 inhibition), hypoxia (through hypoxia inducible factor stabilization), oxidative stress (through ROS), and acidic pH (through AMPK activation and MTORC1 inhibition). 69,108,109 The tumor cell microenvironment influences the regulation of autophagy and energy metabolism not only in cancer cells but also in stromal cells. Thus, the accumulation of ROS in the microenvironment of the tumor cell promotes autophagy in surrounding stromal cells, leading to an influx of nutrients (including glutamine) from stromal cells to cancer cells.…”
Section: Regulation and Role Of Autophagy In Cancer Cellsmentioning
confidence: 99%